Comparison of intraocular pressure (IOP) measured by schiotz indentation and goldmann applanation tonometer: A cross-sectional study - Tanima Bansal; Stuti V Juneja; Isha Gandhi; Moninder Bhati (TNOA Journal of Ophthalmic Science and Research, 2023)
Aim: This cross-sectional study was aimed to compare Schiotz indentation tonometer (ST) and Goldmann applanation tonometer (GAT) readings (in different ranges of IOP) in general population and also to determine the reliability of ST as a tool for mass screening of glaucoma. Material and Methods: This study was conducted on 200 patients who attended the OPD of Ophthalmology in tertiary centre of central Gujarat. The selected population was subjected to detailed anterior segment examination, ocular fundus for optic nerve head and objective determination of IOP of two eyes of the patients. Results: In our study, both GAT and ST showed no statistical difference in IOP between males and females. IOP increased with age. There was no statistical difference between GAT and ST in measuring IOP in range of 7-15 mmHg but ST overestimated GAT in pressure range of 7-15 mmHg. ST underestimated GAT in pressure range of 16-25 mmHg, there was significant difference between GAT and ST in measuring IOP in range of 16-25 mmHg.ST underestimated GAT in IOP reading above 26 mm Hg. Conclusion: In glaucoma screening where we want to detect minor difference between the high normal and abnormal IOP, measurement with ST would be rendered ineffective and it is therefore wise to re-estimate the IOP with GAT and also repeat reading with different weights of ST. But ST being an affordable, easy to maintain, and portable instrument can be used as mass screening tool for glaucoma though at borderline tension between 17 to 23 mmHg it is wise to re-estimate IOP with GAT.